Evaluations of antidepressant activity of Punica granatum peel extract in albino mice - Syeda, Shakira Fathima; G., Sam Pavan Kumar; Mohsin, Mohammed (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Depression is the most common disorder of mental illnesses and affects excess of 10-15% of population. According to the WHO reports, more than 350 million persons suffer from depression all over the world. The aim of present study is to evaluate anti-depressant activity of Punica granatum peel extract (PgPE) in albino mice. Methods: Male albino mice (20-30 g) were used. Animals were divided into 5 groups with 6 animals in each which were subjected to forced swim test. Group 1 is control, group 2 received (standard) imipramine 10 mg/kg, p.o, group 3 (T1) PgPE 50 mg/kg, p.o, group 4 (T2) PgPE 100 mg/kg, p.o, group 5 (T3) PgPE 200 mg/kg, at first animals were forced to swim for 15 min (trained), and the study was performed after 24 hrs. All the animals were treated with individual drug 60 min prior to study, animals were forced to swim for 6 min and the duration of immobility was recorded. The mouse was considered immobile when it floats motionlessly or made only those moments necessary to keep its head above the water surface. The total duration of immobility of each mouse was recorded after the test in each group. Results: The duration of immobility is significantly reduced at PgPE 200 mg/kg and results were analysed by one way analysis of variance (ANOVA). Conclusions: PgPE 200 mg/kg significantly (p<0.05) decreases the duration of immobility in mice.